Oral edaravone demonstrated a favorable safety profile in patients with amyotrophic lateral sclerosis after 48 weeks of treatment. Issue 2 (28th December 2022) - Genge, Angela; Pattee, Gary L.; Sobue, Gen; Aoki, Masashi; Yoshino, Hiide; Couratier, Philippe; Lunetta, Christian; Petri, Susanne; Selness, Daniel; Bidani, Sachin; Hirai, Manabu; Sakata, Takeshi; et al.
Abstract: Introduction/Aims: An intravenous (IV) formulation of edaravone has been shown to slow the rate of physical functional decline in amyotrophic lateral sclerosis (ALS). An oral suspension formulation of edaravone was recently approved by the United States Food and Drug Administration for use in patients with ALS. This study assessed the safety and tolerability of oral edaravone. Methods: This global, open‐label, phase 3 study evaluated the long‐term safety and tolerability of oral edaravone in adults with ALS who had a baseline forced vital capacity ≥70% of predicted and disease duration ≤3 y. The primary safety analysis was assessed at weeks 24 and 48. Patients received a 105‐mg dose of oral edaravone in treatment cycles replicating the dosing of IV edaravone. Results: The study enrolled 185 patients (64.3% male; mean age, 59.9 y; mean disease duration, 1.56 y). The most common treatment‐emergent adverse events (TEAEs) at week 48 were fall (22.2%), muscular weakness (21.1%) and constipation (17.8%). Serious TEAEs were reported by 25.9% of patients; the most common were worsening ALS symptoms, dysphagia, dyspnea, and respiratory failure. Twelve TEAEs leading to death were reported. Forty‐six (24.9%) patients reported TEAEs that were considered related to study drug; the most common were fatigue, dizziness, headache, and constipation. Sixteen (8.6%) patients discontinued study drug due to TEAEs. No serious TEAEs were related to study drug. Discussion: This study indicated that oral edaravone was well tolerated during 48 wk of treatment, with no new safety concerns identified.